Analysis of the Mechanical Properties and Parameter Sensitivity of a U-Shaped Steel Damper - Gao, Jinhe; Xi, Jiahuan; Xu, Yuwen; Ding, Jiajun; Zhu, Junwen; Chang, Yi; Chen, Baokui (Frontiers in Materials, 2021)
To clarify the mechanical properties of the U-shaped steel damper under tension and compression along the opening direction and the energy dissipation mechanism in the energy dissipation system, a mechanical model was established to describe the plastic failure response of the damper, and the formula for theoretical calculation of its mechanical properties was derived. Using the straight line segment length, radius of circular arc and opening direction as parameters for testing four specimens, through the design of reasonable pulling and pressing fixture, four specimens were tested for tension and compression. The initial stiffness and yield load test results and theoretical analysis were good and verified that the opening direction of the U-shaped steel damper affected its mechanical performance. Further analysis of the U-shaped steel damper’s mechanical properties using numerical finite element analysis of the arc radius and the straight line segment length, width and thickness in relation to the initial stiffness shows that increasing the straight section length and end arc radius can reduce initial stiffness , and increase the thickness and width can increase initial stiffness.